Impacts of vehicle emission from a major road on spatiotemporal variations of neighborhood particulate pollution—A case study in a university campus. (February 2020) - Liu, Jiying; Cai, Wei; Zhu, Shengwei; Dai, Fei
Highlights: Both fixed-site and mobile measurements were conducted in a university campus. Spatial and temporal PM concentration variations were investigated. Impacts of vehicle emission from the major road on in-campus PM pollution were studied. PM pollution in the campus due to vehicle emission was great at low background PM levels. The influence range of vehicle emission could be up to 600 m away from the major road. Abstract: Spatial and temporal variations of traffic-related particulate pollution, e.g. PM1.0, PM2.5, and PM10, were monitored in a university campus in Wuhan, China with mobile and fixed-site approaches. We repeated mobile measurements when there was a high vehicle volume on the major road near the campus and only few traffic in the campus. PM concentrations and GPS coordinates were tracked to plot the spatial distributions of PM concentrations on the streets in the campus. Meanwhile, we carried out the fixed-site monitoring to characterize temporal variation of PM concentrations on the rooftop of two four-floor buildings in the campus, one 140 m and another 700 m away from the major road. Results showed that vehicle emission from the major road could contribute a large portion of PM pollution in the campus, especially with a low background concentration. PM concentration decreased rapidly when it was about 180 m away from the major road. The spatial decays of PM10 and PM2.5 concentrations were faster than that of PM1.0 concentration. Moreover, the hourly variations of PM concentrations indicated to be correlated with the traffic volume on the major road. This study provided a valuable suggestion for design and planning of urban green infrastructure.